2010
DOI: 10.1007/s10725-009-9440-6
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic parameters and carbon reserves of a resurrection plant Reaumuria soongorica during dehydration and rehydration

Abstract: The effects of dehydration and subsequent rehydration on photosynthetic parameters and carbon reserves were investigated in the resurrection plant Reaumuria soongorica. Dehydration was imposed by withholding water and covering plants with a PVC sheet when it rained, over a period of 53 days, by which time all leaves had been shed. Thereafter, plants were watered at 7-day intervals. The diurnal course of the net photosynthetic rate (Pn) was bimodal under well-watered conditions. After a period of withholding wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
(27 reference statements)
1
14
0
Order By: Relevance
“…Also, all of the core components were found in the circadian rhythm pathway (Ko04712, 192 unigenes), which is crucial for timing of flower and budset in response to the seasonal rhythm of temperature and light length [37], [38] (File S1). R. soongorica has been regarded as a C 3 plant based on the photosynthesis characteristics [39], but all the core genes of C 4 carbon fixation were found in our transcriptome, surprisingly (Ko00710, 155 unigenes, File S2). Absisic acid (ABA) is a crucial hormone involved in many stress responses [40].…”
Section: Resultsmentioning
confidence: 89%
“…Also, all of the core components were found in the circadian rhythm pathway (Ko04712, 192 unigenes), which is crucial for timing of flower and budset in response to the seasonal rhythm of temperature and light length [37], [38] (File S1). R. soongorica has been regarded as a C 3 plant based on the photosynthesis characteristics [39], but all the core genes of C 4 carbon fixation were found in our transcriptome, surprisingly (Ko00710, 155 unigenes, File S2). Absisic acid (ABA) is a crucial hormone involved in many stress responses [40].…”
Section: Resultsmentioning
confidence: 89%
“…However, the ability to rapidly replace any leaf material lost during desiccation would also seem likely to be advantageous. Studies in the resurrection plant Reaumuria soongorica have indicated the importance of carbon reserves to support vegetative regrowth following rehydration (Xu et al 2010). Our analysis of the transcripts that accumulate to high levels in dried tissues of a resurrection plant have revealed that several of these transcripts encode gene products related to proteins that have been implicated in positively regulating growth associated processes in plants.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, R. soongarica is recognized as an important forage species and major source of salt for livestock (Yang et al, 2015). Previous studies on this species have mainly focused on its morphology and anatomy (Liu et al, 2007;Wang et al, 2011a), genetic diversity (Yang et al, 2015), stress-resistance mechanisms (Xu et al, 2010), and adaptive strategies to desiccation (Wang et al, 2011b). Despite some demonstrated the links between seed germination and the seedling emergence with changes in water availability in R. soongarica, the relationships among seedling emergence, growth, and seedling recruitment in this species with precipitation variability are not entirely understood.…”
Section: Introductionmentioning
confidence: 99%